Interaksi budaya India & Cina ke atas pengukuhan bahasa dalam Tamadun Melayu - ZawiahMat,; Mashitah Sulaiman, (Universiti Kebangsaan Malaysia, 2007)
The history of human civilization depicts that the growth and downfall of a civilization is interrelated to the power and solidarity of its language. Language is an important factor in determining positive interaction within individuals in a society. The migration of the Indian and Chinese community to the Malay Archipelago had led to the strengthening of the Malay language and its civilization. Historians of ancient civilization, elucidate that language plays a crucial role in fostering relations between the speaker and others. The people of the Peninsular of Malaya started interacting using various languages like Malay, Chinese and Tamil. This led to the accommodation and assimilation of culture and the sprucing up of the Malay vocabulary. Thus, this article describes the history of the migration of the Indian and Chinese community to the Malay Archipelago and their interaction with the language, culture and the build-up of the Malay civilization. Besides, this article also discusses about the loan words from the different ethnic groups which have enriched the Malay language